2019
DOI: 10.1111/gcb.14811
|View full text |Cite
|
Sign up to set email alerts
|

Integrating patterns of thermal tolerance and phenotypic plasticity with population genetics to improve understanding of vulnerability to warming in a widespread copepod

Abstract: Differences in population vulnerability to warming are defined by spatial patterns in thermal adaptation. These patterns may be driven by natural selection over spatial environmental gradients, but can also be shaped by gene flow, especially in marine taxa with high dispersal potential. Understanding and predicting organismal responses to warming requires disentangling the opposing effects of selection and gene flow. We begin by documenting genetic divergence of thermal tolerance and developmental phenotypic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 149 publications
(169 reference statements)
4
69
2
Order By: Relevance
“…Accumulated stress beyond a critical threshold results in mortality due to the degradation of cellular components and disruption of physiological functioning (Feijão et al, 2018, Lesser, 2006, Magozzi & Calosi, 2015, Schroda et al, 2015. Although exposure to nonlethal temperatures can also increase tolerance to further stress in some marine organisms (Clapp et al, 1997, Magozzi & Calosi, 2015, Sasaki & Dam, 2019, we do not find evidence for this in our experiment. Instead, we find that experimental populations grown at 5.8 o C (above Topt) prior to heatwave exposure had higher levels of mortality than those grown at 2.5 o C (below Topt), in both the heatwave and control treatments.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Accumulated stress beyond a critical threshold results in mortality due to the degradation of cellular components and disruption of physiological functioning (Feijão et al, 2018, Lesser, 2006, Magozzi & Calosi, 2015, Schroda et al, 2015. Although exposure to nonlethal temperatures can also increase tolerance to further stress in some marine organisms (Clapp et al, 1997, Magozzi & Calosi, 2015, Sasaki & Dam, 2019, we do not find evidence for this in our experiment. Instead, we find that experimental populations grown at 5.8 o C (above Topt) prior to heatwave exposure had higher levels of mortality than those grown at 2.5 o C (below Topt), in both the heatwave and control treatments.…”
Section: Discussioncontrasting
confidence: 73%
“…In phytoplankton, acclimation can alter organismal fitness in the new environment over several asexual generations, and is reversible if the environmental cue stops (Anning et al, 2001, Brand et al, 1981, Kremer et al, 2018. Across a wide variety of marine taxa, numerous studies have demonstrated that previous acclimation to elevated temperatures can enhance tolerance (heat hardening) when exposed to thermal extremes (Hughes et al, 2019, Magozzi & Calosi, 2015, Pansch et al, 2018, Sasaki & Dam, 2019, Scharf et al, 2015, Stuhr et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the temperature and salinity measurements made at the time of collection, we also estimated the thermal environment experienced by individuals during development, as this has been shown to strongly influence thermal tolerance in adult copepods (Pereira et al., 2017; Sasaki & Dam, 2019). However, like other copepods, Acartia species exhibit an exponential relationship between temperature and development time (Kleppel et al., 1996; Mauchline, 1998; Miller et al., 1977; Peterson, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…For these collections, both mature females and males were sorted into filtered seawater, which was then slowly brought to 18°C. We chose this temperature because it represents an approximate mean temperature experienced by Acartia tonsa during its growth season, and because Acartia tonsa individuals from a wide range of thermal environments have been shown to survive and reproduce at this temperature (Sasaki & Dam, 2019). Cultures were kept at ambient CO 2 concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…In phytoplankton, acclimation can alter organismal fitness in the new environment over several asexual generations, and is reversible if the environmental cue stops (Brand et al, 1981;Anning et al, 2001;Kremer et al, 2018). Across a wide variety of marine taxa, numerous studies have demonstrated that previous acclimation to elevated temperatures can enhance tolerance (heat hardening) when exposed to thermal extremes (Magozzi and Calosi, 2015;Scharf et al, 2015;Stuhr et al, 2017;Pansch et al, 2018;Hughes et al, 2019;Sasaki and Dam, 2019).…”
Section: Introductionmentioning
confidence: 99%